Adherence to antiretroviral therapy: an empirical test of the information-motivation-behavioral skills model. - Starace, Fabrizio; Massa, Alessandra; Amico, K Rivet; Fisher, Jeffrey D (Health psychology : official journal of the Division of Health Psychology, American Psychological Association, 2006)
Consistent and nearly perfect adherence is considered an essential requirement for HIV-positive patients on antiretroviral therapy (ART) to fully realize its life-extending benefits. The current study evaluated a comprehensive model of ART adherence--the information-motivation-behavioral skills (IMB) model. This model views adherence behavior as a function of the interrelations between adherence-related information, motivation, and behavioral skills. It hypothesizes that adherence-related information and motivation work through adherence-related behavioral skills to affect the initiation and maintenance of optimal ART adherence. In a series of structural equation models, the IMB model's critical constructs and assumptions were evaluated with a sample of 100 HIV-positive patients in clinical care. Across all analyses, the authors found support for the assumptions of the IMB model of ART adherence. Consistent with the model, adherence-related information and motivation related significantly to adherence-related behavioral skills, and behavioral skills related significantly to self-reported optimal adherence. Further, as predicted, the effects of information and motivation on self-reported adherence were mediated by adherence-related behavioral skills. Current study results are explored, and implications for adherence promotion interventions based on the model are discussed.
Keywords: Adult; Aged; Anti-Retroviral Agents; Female; Health Surveys; Humans; Italy; Male; Middle Aged; Models, Theoretical; Motivation; Patient Compliance; Patient Education as Topic